Indonesia's Maritime Foreign Policy Change: from National Interest to Multilateral Leadership - Hidayatullah, Nur Luthfi (SIYAR Journal, 2025)
This research seeks to explain the factors which stimulated Indonesia’s maritime foreign policy change during Jokowi’s leadership, from focusing on national interest during his first term, into multilateral leadership during his second term. The author argues that Indonesia’s maritime foreign policy changed due to the leader’s decision, bureaucratic advocacy, domestic restructuring, and external shock. This research utilizes explanatory qualitative method, with data collection from documentation, and analyzes the study case using Hermann’s foreign policy change concept. This research finds that there are four factors that caused Indonesia’s maritime foreign policy change, which are Jokowi’s vision from Global Maritime Fulcrum towards ASEAN Outlook on the Indo-Pacific, the Indonesian Ministry of Foreign Affair’s advocacy for maritime diplomacy, the Indonesian Ministry of Maritime Affairs and Fisheries’ restructuring, and Covid-19 and the US-China rivalry as external shocks. Those four factors influenced program change in Indonesia’s maritime foreign policy from economic development to international order, problem or goal change from domestic security to regional stability, and international orientation change from national interest towards multilateral leadership.